2016
DOI: 10.1038/ni.3540
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for the IL-2 receptor in Treg cell function

Abstract: Regulatory T (Treg) cells, expressing abundant amounts of the IL-2 receptor (IL-2R), are reliant on IL-2 produced by activated T cells. This feature implied a key role for a simple network based on IL-2 consumption by Treg cells in their suppressor function. However, congenital deficiency in IL-2R results in reduced expression of the Treg cell lineage specification factor Foxp3, confounding experimental efforts to understand the role of IL-2R expression and signaling in Treg suppressor function. Using genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

27
602
4
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 682 publications
(637 citation statements)
references
References 50 publications
(71 reference statements)
27
602
4
4
Order By: Relevance
“…The observation that constitutive STAT-5b activation increased intestinal adenoma size in the Apc Min/1 mouse is consistent with a role for IL-2R--STAT-5 T reg activation in promoting intestinal tumorigenesis [29]. It is noteworthy that constitutive STAT-5b activation abrogated proinflammatory cytokine secretion while modifying expression of cell surface molecules by T lymphocytes [29]. These, taken together, suggest that abrogation of an increased intestinal CD25…”
supporting
confidence: 57%
See 1 more Smart Citation
“…The observation that constitutive STAT-5b activation increased intestinal adenoma size in the Apc Min/1 mouse is consistent with a role for IL-2R--STAT-5 T reg activation in promoting intestinal tumorigenesis [29]. It is noteworthy that constitutive STAT-5b activation abrogated proinflammatory cytokine secretion while modifying expression of cell surface molecules by T lymphocytes [29]. These, taken together, suggest that abrogation of an increased intestinal CD25…”
supporting
confidence: 57%
“…Additionally, the Ikaros transcription factor Helios is known to have STAT-5b as one of its principal targets in mice, stabilizing STAT-5-dependent IL-2 responsiveness [21]. The observation that constitutive STAT-5b activation increased intestinal adenoma size in the Apc Min/1 mouse is consistent with a role for IL-2R--STAT-5 T reg activation in promoting intestinal tumorigenesis [29]. It is noteworthy that constitutive STAT-5b activation abrogated proinflammatory cytokine secretion while modifying expression of cell surface molecules by T lymphocytes [29].…”
mentioning
confidence: 71%
“…However, at low physiologic concentrations, IL-2 is a critical homeostatic cytokine that is required for normal Treg development, expansion, activity, and survival. [89][90][91] In a phase 1 clinical trial, daily administration of IL-2 at a dose of 1 3 10 6 IU/m 2 per day was demonstrated to be safe and well tolerated in patients with steroid-refractory chronic GVHD. Notably, daily IL-2 treatment at this low dose selectively enhanced CD4…”
Section: Enhancement Of Cd4 Tregs In Vivomentioning
confidence: 99%
“…While it is generally assumed that continued IL-2 signaling is needed for Treg survival, suppressor function, and lineage maintenance, these inferences have largely been extrapolated from germline knockout models, blocking antibody experiments, and in vitro studies. The roles of continued IL-2 signaling following Treg development, and the signals by which IL-2 executes these roles, remain imperfectly understood (Chinen et al, 2016). …”
Section: Introductionmentioning
confidence: 99%